Diversity of Sonneratia alba in coastal area of Central Java based on isozymic patterns of esterase and peroxidase - AHMAD DWI SETYAWAN (Nusantara Bioscience, 2009)
Abstract. Setyawan AD. 2009. Diversity of Sonneratia alba in coastal area of Central Java based on isozymic patterns of esterase and peroxidase. Nusantara Bioscience 1: 92-103. The study was intended to observe the diversity and the relationship of Sonneratia alba in southern and northern coast of Central Java Province based on isozymic patterns of esterase and peroxidase. This research was conducted in July until December 2003, at six sites, i.e. Wulan (WUL), Juwana (JUW), Pasar Bangi (PAS), in the northern coast, and Bogowonto (BOG), Motean (MOT), and Muara Dua (MUA) in the southern coast. The laboratory assay was conducted in Central Laboratory of Mathematics and Natural Sciences, Sebelas Maret University (UNS) Surakarta. The seedling plant samples that were collected from six mangrove habitats transplanted in greenhouse in the laboratory. There were 20 individual samples each site. The result indicated that the individual of S. alba of the same or near location has the same genetic diversity in common, because the genetic exchange on the same population was higher than on a different population. Therefore, the populations of S. alba from northern coast had higher similarity each other than southern coast one, on the other way the populations from southern coast had higher similarity each other than northern coast one.